2021
DOI: 10.3390/jcm10184113
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Low Levels of Parathyroid Hormone after Surgery for Thyroid Cancer: A Single Center Study

Abstract: Background: Thyroidectomy is the definitive treatment for most patients with thyroid cancer. Hypoparathyroidism is the most frequent complication of thyroidectomy, and its pathogenesis is multifactorial. The aim of this study is to evaluate the patient- and surgical-related risk factors for hypoparathyroidism after surgery for thyroid cancer. Methods: In this retrospective study, patients referred to surgery for thyroid cancer from 2016 to 2019 were enrolled. Preoperative serum calcium and parathyroid hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Our study, comprising 343 patients who underwent thyroid surgery, offers several valuable insights into the incidence and risk factors associated with postthyroidectomy hypoparathyroidism. The incidence of postsurgical hypoparathyroidism was 37.90%, which is on the higher end but within the range reported by other studies [5, 14]. Two‐thirds of the participants who developed hypoparathyroidism recovered, mainly within the first month.…”
Section: Discussionsupporting
confidence: 80%
“…Our study, comprising 343 patients who underwent thyroid surgery, offers several valuable insights into the incidence and risk factors associated with postthyroidectomy hypoparathyroidism. The incidence of postsurgical hypoparathyroidism was 37.90%, which is on the higher end but within the range reported by other studies [5, 14]. Two‐thirds of the participants who developed hypoparathyroidism recovered, mainly within the first month.…”
Section: Discussionsupporting
confidence: 80%
“…Although female gender was reported as a risk factor for transient hypoparathyroidism in some studies, no correlation was found between hypoparathyroidism and gender in other studies. [ 33 - 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, there are studies demonstrating no relationship between age and hypoparathyroidism. [ 35 - 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1743 articles were screened (Figure 1) and 237 full‐text articles were assessed for eligibility. After careful selection of the articles, 66 studies were eligible for the final synthesis and were included in this review 10,14,23,24,27‐88 …”
Section: Resultsmentioning
confidence: 99%